2000
DOI: 10.1097/00008506-200010000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Consequences of Three Tracheostomy Techniques

Abstract: We describe the effects of different tracheostomy techniques on intracranial pressure (ICP), cerebral perfusion pressure (CPP), and cerebral extraction of oxygen. We attempted to identify the main mechanisms affecting intracranial pressure during tracheostomy. To do so we conducted a prospective, block-randomized, clinical study which took place in a neurosurgical intensive care unit in a teaching hospital. The patients studied consisted of thirty comatose patients admitted to the intensive care unit because o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…Percutaneous dilational tracheostomy was performed through a 1.5-cm transverse incision at the second of third cartilaginous interspace using a modification [23] of the procedure initially described by Ciaglia et al [24], with the Cook Ciaglia Blue Rhino PT kit. Because of concern for hypoventilation and elevated ICP [13,[17][18][19] associated with bronchoscopy, capnography was routinely used to verify tracheal positioning of the tube [25], with bronchoscopy available for evaluation of the airway or tracheostomy placement, if necessary. All patients received assist control mode ventilation and FiO 2 1.0 throughout the procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous dilational tracheostomy was performed through a 1.5-cm transverse incision at the second of third cartilaginous interspace using a modification [23] of the procedure initially described by Ciaglia et al [24], with the Cook Ciaglia Blue Rhino PT kit. Because of concern for hypoventilation and elevated ICP [13,[17][18][19] associated with bronchoscopy, capnography was routinely used to verify tracheal positioning of the tube [25], with bronchoscopy available for evaluation of the airway or tracheostomy placement, if necessary. All patients received assist control mode ventilation and FiO 2 1.0 throughout the procedure.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of tracheostomy is high among the population served by neurocritical care physicians, including a significant number of patients with ischemic stroke [11], intracerebral hemorrhage [12], subarachnoid hemorrhage [13], traumatic brain injury [14][15][16], hypoxic-ischemic encephalopathy, and status epilepticus. Neurointensivists may be more vigilant in recognizing and managing subtle dangers to brain injured patients that may occur during the procedure, such as hypoventilation, head-down positioning, hypoxia, hypotension, and elevated intracranial pressure (ICP) [13,[17][18][19]. Finally, tracheostomy decreases the work of breathing [20], and early tracheostomy is increasingly recognized as a potential method for reducing the duration of mechanical ventilation (DMV), the frequency of ventilator-associated pneumonia (VAP), intensive care unit length of stay (ICU LOS), and mortality [21,22] among patients who require prolonged mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined influence of PDT on the ICP and CPP, showing variable results [3][4][5][6]. Some authors detected elevation of mean ICP during PDT, while others did not.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Stocchetti et al 15 was not included because of a lack of information relating to outcome. Study characteristics, events, and quality of evaluation of each selected study are shown in Tables 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…However, I differ from their approach. I excluded one of the trials they included, 15 so data about events and number of total complications were different from this study. Although Cabrini et al 9 found a high statistical heterogeneity, they accepted the pooled result, which is not recommended by meta-analysis experts.…”
Section: Discussionmentioning
confidence: 99%